الدولة الريعية في البلدان العربية - الزازية، ستيتي (جامعة غرداية, 2015)
تعتبر الدولة "ريعية" لا لكونها تنتج البترول وتعتمد عليه في اقتصادها فحسب، بل لكونها تدير عملية بيعه وإنفاقه لوحدها وبالطريقة التي تشاء، وإن قيام الدولة الريعية في البلدان العربية ودول الخليج بشكل خاص ألقى بآثاره على طبيعة دور الدولة وسلوك الأفراد كغياب الديمقراطية وتدوير الجزء الأهم من الريع البترولي لصالح الدول الغربية، وسيادة العقلية الريعية على المجتمع وتحويله إلى هرم من الشرائح الريعية المتتابعة الذي تغيب فيه علاقات الإنتاج وتغلب عليه علاقات التوزيع.
Renter state is not just` because it does not produce oil and rely on it only in its economy, but because it manages to sell it and spend it on their own process and the way it wants. If the renter state in the Arab countries and the Gulf states in particular threw effects on the nature of the role of the state and the behavior of individuals, such as the lack of democracy and recycling of the most important petroleum royalty in favor of the Western countries, and the rule of renter mentality on society and turn it into a pyramid of renter slides in a row in which the absence of relations of production and distribution relationships beat it.
Keywords: النفط -- الدولة الريعية -- الدول العربية